Analysis of the development trends and innovation characteristics of Internet of Things technology – based on patentometrics and bibliometrics. Issue 1 (2nd January 2020) - Li, Xiang; Pak, Chanil; Bi, Kexin
ABSTRACT: The Internet of Things technology has entered a stage of rapid development, and the development trends and innovative features of it are worth exploring in depth. The purpose of this paper is to provide a comprehensive analysis of the current research focus and innovation characteristics of the Internet of Things technology, and it puts forward policy recommendations for countries in the future development. In this paper, the Internet of Things technology based on Scopus database is divided into five technical sub-fields by means of bibliometric. Patentometrics is used to make the systematic analysis of Internet of Things Technology and its various technical sub-fields based on Derwent Patent Database, and the analysis explores the innovative features of Internet of Things technology and its various technical sub-fields. Research shows that the research focus and innovation characteristics of countries in the Internet of Things technology are not the same.